The double sequences spaces cP2(p) and c2PB(p) - Gökhan, A; Çolak, R (Elsevier Science Inc, 2004)
In this paper we introduce and examine some properties of the double sequence spaces c(2)(P)(p) and c(2)(PB)(p). (C) 2003 Elsevier Inc. All rights reserved.
Keywords: double sequences; double series; double limit